Intercalation of Azo Dyes in Ni-Al Layered Double Hydroxides - Saikia, Hemaprobha; Nath Ganguli, Jatindra (Asian Journal of Chemistry, 2012)
Ni-Al layered double hydroxides were synthesized by hydrothermal process and intercalated with azo dyes viz. metanil yellow, sunset yellow and amaranth by anion exchange process. The resulting hybrid intercalated solid compounds were characterized by powder XRD, FTIR, DRS and TGA. The powder X-ray diffraction revealed the presence of supramolecular host-guest interaction between the host matrix and interlayer anionic dye guest with an expanded interlayer distance. The TGA studies showed that the dye-intercalated layered double hydroxides had higher thermal stability than the pristine dye. Moreover, there was no significant change in the UV-VIS/DR spectra of the dye-intercalated sample after heating up to 200 ºC, indicating that the thermal stability of dye is markedly enhanced by the intercalation into the gallery domain of NiAl-LDH.